(untitled) (Journal of the College of Languages (JCL), 2025)
Considering the importance of researches in the area of comparing different languages and its impact on discovering languages links, the present study examines Arabic prepositions (Harf Jar) and Persian preposition in the place of one of the most important element of grammar in two languages based on the studies conducted by the grammar researchers of Arabic and Persian languages, in order to make the 2 languages’ differences, similarities and their impact on each other more obvious. One of the most important discovery of this study is that, it indicates that each prepositions has a primary meaning with two or more implications, so using each one of these prepositions in another place is almost impossible.